Nurses' perceptions of critically ill patients' eye care: a qualitative study in Iran - Maryam Askaryzadeh Mahani; Jamileh Farokhzadian; Fatemeh Bahramnezhad; Monirsadat Nematollahi (BMC, 2023)
Abstract Background Despite the high prevalence of ocular complications in patients admitted to the intensive care unit (ICU), eye care, as an important component of the care plan, has not received much attention from nurses. To improve the quality of eye care, the challenges and concerns of ICU nurses should be studied deeply. Thus, the present study aimed at exploring the challenges faced by ICU nurses in taking care of patients admitted to the ICU. Methods The present conventional qualitative content analysis study was carried out on 11 nurses and 3 head nurses selected purposefully by observing the maximum variation. The data were collected through face-to-face, in-depth, and semi-structured interviews. All data were recorded, transcribed, and analyzed using the conventional content analysis method proposed by Graneheim and Lundman (Nurse Educ Today 24:105-12, 2004). The Max Q Data software 2020 was run to record the interviews and extract codes from the transcriptions. Results The participants' mean age was 37.14 ± 6.41 years and their average work experience in ICU was 10.29 ± 7.63 years. The core category that emerged from data analysis was "the lack of an evidence-based approach", which was subdivided into five categories: "education, the missing link", "nurses' inadequate professional competence", "unsafe nursing care", "organizational requirements", and "difficulty in eye care evaluation". Conclusion Evidence-based practice plays a minor role in the field of eye care in Iran, despite its critical importance. Thus, the Ministry of Health and Medical Education of Iran is recommended to adapt the clinical guidelines so that more attention is paid to this field.